Teacher Competence and Learning Facilities in Supporting Junior High School Teacher Performance - Muchtar Ahmad; Abdul Rahmat (Global Scientific Publishing, 2023)
This research aims to determine the influence of teacher competence and learning facilities on teacher performance. Operationally, this research aims to determine partially and simultaneously "The influence of teacher competency and learning facilities on the performance of junior high school teachers in Tolinggula District, North Gorontalo Regency. This research uses a quantitative survey type method. This research data was obtained by distributing questionnaires to 33 teachers as respondents. Research data comes from primary data with statistical analysis using SPSS. The results of this research can be concluded that the partial influence of competence (X1) on teacher performance (Y) is 0.975 or 97.5%, this is acceptable because teacher competence (X1) is very significant in strengthening the success of teacher performance in the classroom and outside the classroom which determines teacher performance at the Tolinggula District Level, North Gorontalo Regency. Statistically, it shows that competence has a very important influence in improving teacher performance, this is the basic capital for teachers to improve the quality and quality of education professionally to increase professional teacher performance. The partial influence of learning facilities (X2) on teacher performance (Y) is 0.014, this is acceptable because learning facilities (X2) are not the only parameter that determines teacher performance at the Tolinggula District Level, especially at the junior high school level in North Gorontalo Regency. . Statistically, it shows that learning facilities do not have an important influence on improving teacher performance, this is because the character of the teacher himself is better than before. Taken together, research on the influence of teacher competency and learning facilities simultaneously on teacher performance is 0.968 or 96.8%. Meanwhile around 3.2% was influenced by other factors not included in the research model. This is understandable because teacher performance is not only determined by teacher competency and learning facilities, because other factors are also very likely to influence teacher performance, for example the work environment, certified teacher leadership, teacher education qualifications and teacher motivation so it can be concluded that The overall influence of competency and learning facilities on teacher performance is 96.8% acceptable.
Keywords: Competence; Learning Facilities; Teacher Performance